Biochar and Compost-Based Integrated Nutrient Management: Potential for Carbon and Microbial Enrichment in Degraded Acidic and Charland Soils - Rahman, M. M.; Islam, Md. Rafiqul; Uddin, Shihab; Rahman, Mohammad Mahmudur; Gaber, Ahmed; Abdelhadi, Abdelhadi A.; Jahangir, M. M. R. (Frontiers in Environmental Science, 2022)
Soil acidification and charland formation through alluvial sand deposition are emerging threats to food security in Bangladesh in that they endanger crop production in about 35% of its territory. The integrated plant nutrient system (IPNS) is a globally accepted nutrient management approach designed to revive the damaged soils’ fertility level. Total organic carbon (TOC) in soil is a composite index of soil quality that has consequences for agricultural productivity and natural soil ecosystems. This study assesses the impacts of using biochar, compost, poultry litter, and vermicompost-based IPNS approaches on labile and TOC pools, TOC stocks, lability and management indices, and microbial populations under different cropping patterns after 2 years in acidic and charland soils. The application of IPNS treatments increased microbial biomass carbon (MBC) by 9.1–50.0% in acidic soil and 8.8–41.2% in charland soil compared to the untreated soil, with the largest increase in poultry manure biochar (PMB). Microbial biomass nitrogen (MBN) rose from 20 to 180% in charland soil compared to the control, although no effect was observed in acidic soil. Basal respiration (BR) rose by 43–429% in acidic soil and 16–189% in charland soil compared to the control, exhibiting the highest value in PMB. IPNS treatments significantly improved SOC and POC but did not affect POXc and bulk density in both soils. The PMB and organic fertilizer (OF, compost)-based IPNS wielded the greatest influence on the lability index of MBC in acidic soils and the management index of MBC in both soils. This is despite the fact that IPNS did not affect the lability and management indices of active carbon (AC). IPNS treatments increased the stocks of SOC and MBC in both the soils and POC stock in acidic soil. IPNS treatments significantly boosted the bacterial and fungal populations in both soils, despite having no effect on phosphorus-solubilizing bacteria (PSB). Thus, PMB and OF (compost)-based IPNS may be a better nutrient management practice in degraded acidic and charland soils. This is especially the case in terms of soil quality improvement, soil carbon sequestration, and microbial enrichment.